Abundance And Distribution Of Plastic Debris In Beach Sediment And Seawater Of The Northern Straits Of Malacca - Lim, Er Vin (2024)
Plastics account for 60% - 80% of marine debris worldwide and Malaysia is the top three plastic polluter country in the world through river pathway to marine environment in 2021. A comprehensive database of the status of plastic pollution in Malaysia is needed to help in achieving better management of plastics, such as the plan in Malaysia’s Roadmap toward Zero-Single-Use Plastics 2018-2030 and Plastics Sustainability Roadmap 2021-2030. This study aims to record the abundance of macro- (> 2.5 cm) and meso-plastic (0.5 – 2.5 cm) debris at selected beaches and microplastics (<0.5 cm) at selected sea surface in the northern Straits of Malacca. All study sites are publicly accessible beaches (Pulau Songsong, Teluk Aling, and Pulau Gazumbo) except Pulau Lembu which is in a Marine Protected Area (MPA). The debris was collected from predetermined transects on the beach and categorised according to its size, form and economic market segments in Malaysia. Most of the macro- (53 – 75% of total mass; p=0.0277, α<0.05) and meso-plastics (53 – 80% of the total number) were accumulated at the backshore area. Public beaches such as Pulau Gazumbo (7.32 ± 9.90 g/m2) and Pulau Songsong (9.77 ± 11.35 g/m2) recorded the highest mass of macroplastics per area by zone. Teluk Aling recorded the lowest mass of macroplastics per area by zone (3.58 ± 3.21 g/m2) but the highest in mesoplastic (0.56 ± 0.60 item/m2). By number, the highest number of macroplastics per area by zone was found at Teluk Aling (1.10 ± 1.29 item/m2) and Pulau Lembu (1.19 ± 0.30 item/m2), while the lowest was found at Pulau Gazumbo (0.44 ± 0.61 item/m2).